Effects of dietary Bacillus coagulans on the productive performance, egg quality, serum parameters, and intestinal morphology of laying hens during the late laying period - Xiaoming Wang; Huafeng Jian; Wenyan Zhao; Jiankui Li; Xiaoting Zou; Xinyang Dong (Italian Journal of Animal Science)
The aim of this study was to investigate the effects of Bacillus coagulans (B. coagulans) on the productive performance, egg quality, blood biochemistry, antioxidant capacity, reproductive hormones, immune function, and intestinal morphology of laying hens (86 weeks old) during the late laying period. A total of 960 Hy-Line Brown layers were randomly assigned to five treatment groups, each with 6 replicates of 32 hens. Hens were grouped as follows: basal diet (control group) and a basal diet supplemented with 3.25 × 105, 6.5 × 105, 9.75 × 105, or 1.3 × 106 cfu/g B. coagulans. Dietary supplementation with B. coagulans significantly enhanced egg mass, egg weight, and laying rate and decreased the feed conversion ratio (FCR) in comparison with the control group. No significant difference was observed in the feed intake, breaking rate, albumen height, haugh unit, egg yolk colour, eggshell strength, and eggshell thickness among all groups. The serum total protein (TP) levels of laying hens fed 6.5 × 105 cfu/g B. coagulans were higher than those of laying hens in the control group. Dietary supplementation with 3.25 × 105 cfu/g and 6.5 × 105 cfu/g B. coagulans improved the activity of glutathione peroxide (GSH-Px) compared with that of the control group. The serum IgA concentration of laying hens in the 1.3 × 106 cfu/g B. coagulans treatment group was higher than that of the control. In the ileum, 6.5 × 105 cfu/g B. coagulans supplementation significantly increased the ratio of villus height to crypt depth (VH/CD) compared to that of the control group. It can be concluded that B. coagulans, at a supplementation level of 6.5 × 105 cfu/g feed, can be used as an effective feed additive to improve the production performance of laying hens during the late laying period by increasing the serum TP level, serum GSH-Px activity, and ileal VH/CD ratio.HIGHLIGHTS Bacillus coagulans improved the productive performance of laying hens during the late laying period. Inclusion of Bacillus coagulans in the diet might benefit laying hens’ health by improving blood biochemistry, enhancing antioxidant activity and intestinal morphology, and slightly enhancing immune ability. The optimum concentration of Bacillus coagulans as a supplement to the basal diet to promote production performance and improve host health is 6.5 × 105 cfu/g.